2009
DOI: 10.1007/s12104-009-9195-z
|View full text |Cite
|
Sign up to set email alerts
|

Backbone resonance assignments of a promiscuous aminoglycoside antibiotic resistance enzyme; the aminoglycoside phosphotransferase(3′)-IIIa

Abstract: The aminoglycoside phosphotransferase(3')-IIIa (APH) is a promiscuous enzyme and renders a large number of structurally diverse aminoglycoside antibiotics useless against infectious bacteria. A remarkable property of this approximately 31 kDa enzyme is in its unusual dynamic behavior in solution; the apo-form of the enzyme exchanges all of its backbone amide protons within 15 h of exposure to D ( 2 ) O while aminoglycoside-bound forms retain approximately 40% of the amide protons even after >90 h of exposure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Such behavior appears to be common with aminoglycoside modifying enzymes because we also observed similar aminoglycoside-dependent spectral changes in dynamic properties of a different enzyme, the aminoglycoside phosphotransferase(3)-IIIa. 7,24 Previous data acquired by isothermal titration calorimetry (ITC) indicated that CoASH is able to increase antibiotic binding affinity to AAC in an antibioticdependent manner that varies from 4-fold up to 15-fold, 5 providing additional evidence that there is a link between these two distinct ligand binding sites. It is likely that binding of CoASH to AAC causes conformational changes in the aminoglycoside binding site, which also affects dynamic properties of some backbone amides.…”
Section: Coash Interaction With Aac Implies Dynamicsmentioning
confidence: 99%
“…Such behavior appears to be common with aminoglycoside modifying enzymes because we also observed similar aminoglycoside-dependent spectral changes in dynamic properties of a different enzyme, the aminoglycoside phosphotransferase(3)-IIIa. 7,24 Previous data acquired by isothermal titration calorimetry (ITC) indicated that CoASH is able to increase antibiotic binding affinity to AAC in an antibioticdependent manner that varies from 4-fold up to 15-fold, 5 providing additional evidence that there is a link between these two distinct ligand binding sites. It is likely that binding of CoASH to AAC causes conformational changes in the aminoglycoside binding site, which also affects dynamic properties of some backbone amides.…”
Section: Coash Interaction With Aac Implies Dynamicsmentioning
confidence: 99%